Dinamika Dakwah Islam Dalam Menghadapi Tantangan Di Era Digital: Perspektif Nahdlatul Ulama Dan Muhammadiyah - Nadiyah, Nur Rifqah; Muh. Nur Rochim Maksum (Program Studi Komunikasi dan Penyiaran Islam, 2024)
The digital era has brought changes to Islamic da'wah, providing various challenges. NU and Muhammadiyah can also have different strategic perspectives and approaches in preaching in the digital era. This research aims to find out what the challenges are for Islamic da'wah in the digital era and what are the strategies of NU and Muhammadiyah in dealing with da'wah in the digital era. The research method is qualitative in the form of a literature study with a descriptive approach. The data collection technique is documentation. The research results show that NU and Muhammadiyah are both responding and innovating in da'wah in the digital era. NU is active on various social media such as Instagram, Twitter, Facebook, YouTube, and da'wah on the NU Online site which is always existing and significant, as well as launching the podcast program